1988
DOI: 10.1254/jjp.48.349
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Profiles of CS-622, a Novel Angiotensin Converting Enzyme Inhibitor

Abstract: Abstract-CS-622is a prodrug type ACE inhibitor with a thiazepin ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 8 publications
2
20
0
Order By: Relevance
“…CS-622 diacid was used in vitro because CS-622 is converted to the active diacid in vivo. As described elsewhere, 22 CS-622 diacid at a concentration of 3xlO~8 M completely abolished the contraction induced by angiotensin I (3xlO~8 M) in rat aorta. Therefore, 10~5 M of CS-622 diacid was considered sufficient to inhibit ACE of the aortic smooth muscle.…”
Section: Contractile Responses To Cgp-28392 In the Isolated Aortassupporting
confidence: 55%
“…CS-622 diacid was used in vitro because CS-622 is converted to the active diacid in vivo. As described elsewhere, 22 CS-622 diacid at a concentration of 3xlO~8 M completely abolished the contraction induced by angiotensin I (3xlO~8 M) in rat aorta. Therefore, 10~5 M of CS-622 diacid was considered sufficient to inhibit ACE of the aortic smooth muscle.…”
Section: Contractile Responses To Cgp-28392 In the Isolated Aortassupporting
confidence: 55%
“…Drugs CS-866 (20), a selective non-peptide angiotensin AT1 receptor antagonist, and temocapril hydrochloride (21), an angiotensin-converting enzyme (ACE) inhibitor, were synthesized by Sankyo Co., Ltd. (Tokyo, Japan). These drugs were suspended in 0.5% carboxymethylcellulose (CMC).…”
Section: Methodsmentioning
confidence: 99%
“…CS-622 is a selective ACE inhibitor that does not have any other pharmacological actions. 40 Our previous studies showed that long-term administration of CS-622 suppressed the increased Ca 2+ -dependent resting tone and CGP-28392-induced contraction in SHR aorta and that these suppressions were never achieved by either long-term treatment with hydralazine or acute inhibition of aortic ACE in vitro. 15 - 35 In the present study, long-term treatment with CS-622 (10 mg/kg/ day) lowered blood pressure of SHR to the same level as that of WKY rats (Table 1) and lowered both [Ca 2+ ], and resting tone in SHR aortas to levels in WKY rat aortas (Figure 2).…”
Section: Effects Of Nicardipine On Basal Calcium Level and Basal Tensmentioning
confidence: 97%